In-line measurement of pulverized coal concentration and size in pneumatic pipelines using dual-frequency ultrasound. (September 2018) - Gu, Jianfei; Su, Mingxu; Cai, Xiaoshu
Graphical abstract: Highlights: The irregularity of pulverized coal is theoretically investigated based on complex scattering model with fragment correction. Superposed signal excitation is proposed and Hilbert-Huang transform and fast Fourier transform are integrated to implement the effective signal identification and processing. Hilbert-Huang transform and fast Fourier transform are integrated to implement the effective signal identification and processing. Abstract: The influence of pulverized coal irregularity on acoustic attenuation is investigated, the relationship among the ultrasonic attenuation, the volume fraction and size of pulverized coal is established, and the theoretical dependence of retrieved pulverized coal volume fraction and particle size is formed with experimental data. The signal excitation of superposed wave is proposed to boost integration level of the experimental setup at two different frequencies of 40 kHz and 200 kHz for in-line measurement. Then, a comprehensive method integrating Hilbert-Huang transform (HHT) and fast Fourier transform (FFT) is conducted for the effective signal identification during the signal processing. In the meantime, the influences of the designed probes on the flow field are analyzed by numerical simulation. In-line measurements are carried out at different zones/depths of the pneumatic pipelines, including one-hour continuous monitoring. The particle size comparison between imaging and ultrasonic methods shows that the latter is effective, which yields an average deviation of about 15%, and the obtained average volume fraction of pulverized coal is approximately 0.112%.